17-19 ЁШЛИ ГИМНАСТИКАЧИЛАРДА МАХСУС ЖИСМОНИЙ ТАЙЁРГАРЛИКНИ РИВОЖЛАНТИРИШ УСЛУБИЯТИ - Жонкобилов, У.А. (SCIENCE and SOCIETY, 2023)
The article, a variant of pedagogical control aimed at developing a system for evaluating test results and creating integral indicators of physical fitness of gymnasts is scientifically substantiated.The conducted researches showed that the total indicator, which was compiled by summing up the integral indicators of power, speed-strength, coordination readiness, special endurance, has the greatest information content.